Keberlangsungan Kelembagaan di Subak yang Mengalami Alih Fungsi Lahan (Kasus Subak Padang Tegal, Kecamatan Ubud, Kabupaten Gianyar) - HARYASTIKA, I GUSTI NGURAH GEDE; SUARDI, I DEWA PUTU OKA; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.4, Oktober 2016, 2016)
Institutional sustainability of Irrigation Organizations of Subak that Experiencing Land Conversions: A Case Study of Subak of Padang Tegal, Sub-District of Ubud, Gianyar Regency The high land conversions to other uses in Bali have made the agricultural sector should begin to be aware, especially the agricultural stakeholders in the tourist destination. This study aimed to determine the sustainability of institution in the Subak of Padang Tegal, and to find out the life of farmers as members of Subak of Padang Tegal, Sub-District of Ubud. The scope of this study encompasses institutional continuity in Subak that undergoing conversion to other uses. In addition, this study analyzed the life of the farmer members of Subak Padang Tegal who remained carry out activities in the Subak. This study used qualitative descriptive analysis. The research results showed  that institutional sustainability in the Subak of Padang Tegal can still run well. The institutional scores achieved before the trends of land conversion to other uses occurred was 83.8% and only 1.1% decline in institutional water control system at this time. The farmers’ life as members of Subak of Padang Tegal was in middle category. Although still in the good category, it is expected that the institutional Subak of Padang Tegal should be maintained both from internal and external factors.
Keywords: land conversion; institutional of subak; life of farmers